2018
DOI: 10.1055/s-0038-1670674
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hepatic Inflammation via Macrophage Cell Death

Abstract: Macrophages are innate immune cells with diverse functions including clearing infectious agents, inducing inflammation and fibrosis, resolving fibrosis, and restoring tissue integrity. Liver macrophages consist of both resident Kupffer cells and infiltrating macrophages. They have heterogeneous highly plastic phenotypes, and they change their phenotypes rapidly in response to a diverse array of signals present in the injured or recovering liver. Cell death by apoptosis, necroptosis, or pyroptosis is a common r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 159 publications
0
25
0
Order By: Relevance
“…Many studies have reported that the accumulation of hepatic macrophages plays a role in the pathogenesis of liver fibrosis by secreting pro‐inflammatory cytokines such as TNFα . Recent reports have also shown that dysregulated macrophage function contributes to the development of fibrosis and cell death and that apoptosis is a common response of hepatic macrophages to toxic insults . It was also shown that hepatic macrophages undergo apoptosis in fibrotic livers, possibly through the Fas‐mediated pathway .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported that the accumulation of hepatic macrophages plays a role in the pathogenesis of liver fibrosis by secreting pro‐inflammatory cytokines such as TNFα . Recent reports have also shown that dysregulated macrophage function contributes to the development of fibrosis and cell death and that apoptosis is a common response of hepatic macrophages to toxic insults . It was also shown that hepatic macrophages undergo apoptosis in fibrotic livers, possibly through the Fas‐mediated pathway .…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Recent reports have also shown that dysregulated macrophage function contributes to the development of fibrosis and cell death and that apoptosis is a common response of hepatic macrophages to toxic insults. 20,21 It was also shown that hepatic macrophages undergo apoptosis in fibrotic livers, possibly through the Fas-mediated pathway. 22 Another study 23 reported that the apoptosis of M1 hepatic macrophages, which secrete pro-inflammatory mediators such as TNFα, plays a role in the pathogenesis of liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic macrophages undergoing cell death, such as pyroptosis and necroptosis, are often observed during pathogen infection and sterile liver injury, and death of hepatic macrophages represents an important mechanism of bacterial clearance and inflammation resolution. 134 During infection by flagellin-expressing Salmonella typhimurium, Legionella pneumophila or Bukholderia thailandensis, caspase-1-induced pyroptosis of macrophages causes the release of ROS, which subsequently promotes the bacteria-killing activity of neutrophils. 135 Both Listeria monocytogenes and Salmonella enterica induce early rapid necroptosis of KCs in vivo.…”
Section: Roles Of Macrophages In Resolving Inflammation During Liver mentioning
confidence: 99%
“…For what concerns other severe complications of cirrhosis, e.g., portal hypertension-induced ascites, the role of other TAM system members has been demonstrated, with particular regard to MERTK. This prorestorative marker shows a two-faced activity: while for instance it is abundantly expressed in liver macrophages during the resolution phases of several diseases (e.g., acetaminophen-induced liver injury) [121], it has also been identified as a potent suppressor of T cell responses [122]. Regarding the latter activity, there are for instance some pieces of evidence about the development of immunoparesis in patients with acute on-chronic liver failure (ACLF) involving the unbalanced activation and overexpression of MERTK on monocytes/macrophages in the circulation and tissue sites of inflammation [123125].…”
Section: Gas6/tam Receptorsmentioning
confidence: 99%